Religion and Sustainable Development: Analysing the Connections. (17th April 2013) - Narayanan, Yamini; Springett, Delyse
ABSTRACT Religion's role in development has generally been viewed with suspicion, if not indifference, in scholarly and institutional concerns with development planning and policy. The last two decades, however, mark a departure, with a burgeoning interest in religion as a category of analysis in development studies. In this paper, I address the religion–sustainable development nexus specifically, and argue that religion – for both its constructive and destructive potential – must be considered in the sustainable development agenda. Specifically, I identify three ways in which religion may play an important role in enabling sustainable development – through its values, through its potential for social and ecological activism and in the realm of self‐development. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.